Analisis Konten Tiktok @Iben_Ma sebagai Strategi Pemasaran Sambal Bakar - Yunita Tri Rachmayanti; Sumartono Sumartono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research is a synthesis of various sources of information, including research journals, articles, books and TikTok content from the @iben_ma account. The main focus of the research is on the concept of Marketing Strategy, utilization of the TikTok platform and Content Marketing strategy. By combining data from various sources, this research aims to provide a comprehensive understanding of the use of TikTok as an effective marketing tool, especially in the context of marketing products such as Indonesian Sambal Bakar which is promoted by the owner directly @iben_ma. The research results show that the promotional strategy used by @iben_ma on TikTok for Sambal Bakar Indonesia was successful in increasing brand awareness, building positive consumer perceptions, and strengthening relationships with the audience.